Optimization of coaxial magnetic gear and its application in wave power generation - Fang, Hongwei; Li, Ziyan (International journal of applied electromagnetics and mechanics, 2023)
The application of coaxial magnetic gear (CMG) in wave generator instead of traditional variable speed gearbox can effectively improve torque density and reduce torque ripple. Thus, the operation principle of CMG from the perspective of magnetic field modulation is firstly analyzed in this paper. Then the air gap magnetic fields induced by high-speed and low-speed rotors are studied. And the radial height, inner diameter angle, and outer diameter angle of the modulating pieces (MPs) are optimized by using the combination of response surface method (RSM) and particle swarm optimization (PSO) algorithm to improve the torque transmission capacity of CMG. The CMG is combined with the permanent magnet synchronous machine to get the magnetic-gear permanent magnet synchronous generator (MG-PMSG). The design feasibility of the MG-PMSG is verified from four aspects: static magnetic field analysis, no-load characteristics, load characteristics and load disturbance analysis.